The Influence of Social Media Marketing on Decision to Visit Mediated by Fear of Missing Out (FOMO) and Trust - Iqbal, Muh; Abdillah, Yusri; Kholid Mawardi, Mukhammad (FIA UB, 2025)
This study aims to investigate how Social Media Marketing (SMM) affects Visit Decisions and how Fear of Missing Out (FOMO) and Trust act as mediating factors at Florawisata Santerra Delaponte, Malang. This study helps businesses in the tourism sector apply the results to improve tourist decisions and increase the number of visits to the tour. This study was conducted on visitors to Florawisata Santerra Delaponte, Malang. A sample of 162 respondents was selected for this study using a quantitative approach to nonprobability sampling. Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to evaluate the data in this study using SmartPLS 4 software. The results of this study show that the Social Media Marketing (SMM) variable significantly influences the Visiting Decision, and the FOMO variable does not mediate the relationship between the Social Media Marketing (SMM) variable and the Visiting Decision variable. Business actors can utilize the practical implications derived from this research in the related tourism sector to use social media marketing more effectively, thereby helping to improve visiting decisions and enhance tourists' trust, which will ultimately impact increasing visiting decisions.